Diferencias y convergencias entre el pragmatismo peirceano y otros pragmatismos - Reyes, Paniel (2016)
The term “pragmatism” has been used and abused by doctrines that are even contradictory among them. For the founder of Pragmatism as a philosophicaltradition, Charles Peirce, this situation might seem a sad misunderstanding, and that is why he came up with the term “pragmaticism” in order to distinguish his own particular version of Pragmatism. However, Peirce himself did not leave a systematic treaty that explained what kind of specific conditions distinguish his pragmatism from other versions. In this essay I introduce some criteria that I deem fundamental to disambiguate the meaning of Pragmatism: (1) the use of the logical principle known as the ‘pragmatic maxim’, upon which the corner stone of the tradition should rest; (2) the need to adopt Scholastic Realism and reject Nominalism; and (3), the operationalist character (as opposed to the inferential character) of Peirce’s pragmatism. In addition, I offer some views avowing that in spite of the differences and distinctions that these criteria establish, there is a core of convergence between the different kinds of pragmatisms present in the philosophical tradition.